Improvements of nuclease and nickase gene modification techniques for the treatment of genetic diseases - Lu, Yaoyao; Happi Mbakam, Cedric; Song, Bo; Bendavid, Eli; Tremblay, Jacques-P. (Frontiers in Genome Editing, 2022)
There are many hereditary diseases caused by a single base-pair alterations in the genomic DNA. To repair these gene mutations, several nuclease and nickase genome editing strategies have shown great promises. Indeed, in the past decade, the revolution in nuclease-mediated gene modification methods evolved from Zinc-Finger Nucleases (ZFNs) and Transcription Activator-like Effector Nucleases (TALENs) to Clustered Regulatory Interspaced Short Palindromic Repeats (CRISPR). The CRISPR technology has been modified to produce cytidine or adenosine base editing technologies and the PRIME editing technology. In this review, we summarized the recent progress and the remaining gaps for the clinical applications of these genome editing technologies.